A escrevivência como lituraterra - Tayná Celen Pereira Santos (2022)
With this work I propose to think of escrevivência as a Lituraterra. From the peculiar handling of writing made by Conceição Evaristo, the escrevivência, it was possible to notice that, in addition to literature, there would be a dimension of jouissance that approached the understanding of literature proposed by Jacques Lacan in 1971. The dissertation is based, therefore, on the concept of letter, its clues in Freud and formalizations in Lacan, from the 1950s, when the term first appeared as a concept, to the article Lituraterra contained in the elaborations of the 1970s. the proposed objectives are distributed by the chapters of the dissertation. In this way, I conceptualize the escrevivência from its birthplaces and subtexts. Ipropose a theoretical incursion into the concept of letter in Lacan's teaching, in order to operate with the notions proposed in Lituraterra applied to evaristian escrevivência, relaunching them in the field of politics. And, thus, verifying the initial hypothesis that Lituraterra approaches the handling of writing in escrevivência .